Improving Injectable Medicines Prescription in Outpatient Services: A Path Towards Rational Use of Medicines in Iran - Firoozeh Bairami; Fatemeh Soleymani; Arash Rashidian (Kerman University of Medical Sciences, 2016)
Injection is one of the most common medical procedures in the health sector. Annually up to 16 billion injections are prescribed in low- and middle-income countries (LMICs), many of them are not necessary for the patients, increase the healthcare costs and may result in side effects. Currently over 40% of outpatient prescriptions in Iran contain at least one injectable medicine. To address the issue, a working group was established (August 2014 to April 2015) to provide a comprehensive policy brief to be used by national decision-makers. This report is the extract of methods that were followed and the main policy options for improving injectable medicines prescribing in outpatient services. Thirty-three potential policy options were developed focusing on different stakeholders. The panel reached consensus on seven policy options, noting effectiveness, cost, durability, and feasibility of each policy. The recommended policy options are targeted at patients and public (2 policies), insurers (2), physicians (1), pharmacies (1), and the Ministry of Health and Medical Education (MoHME) (1).